The genus Manota Williston (Diptera: Mycetophilidae) in Melanesia and Oceania - Hippa, Heikki (Zootaxa, 2007)
The following new species of Manota are described: M. biunculata (Papua New Guinea), M. evexa (Papua New Guinea), M. explicans (Papua New Guinea), M. gemella (Ambon, Maluku Utara, Indonesia), M. hirsuta (Papua New Guinea), M. orthacantha (Papua New Guinea), M. parilis (Papua New Guinea), M. pentacantha (Solomon Islands), M. perissochaeta (Papua New Guinea and Solomon Islands), M. serawei (Papua New Guinea), M. sicula (Papua New Guinea), M. spathula (Papua New Guinea), M. subspathula (Papua New Guinea) and M. tricuspis (Fiji). Manota ctenophora Matile (New Caledonia), M. maorica Edwards (New Zealand) and M. taedia Matile (New Caledonia) are redescribed. Manota hamulata Colless, previously known from Palau, is redescribed and recorded from Papua New Guinea. Manota pacifica Edwards from Samoa is discussed and compared with the other species of the region. A key to the Melanesian and Oceanian species of Manota is given.